Serum Concentrations of Neuron-Specific Enolase in Dogs Following Traumatic Brain Injury. (August 2020) - Chai, O.; Mazaki-Tovi, M.; Klainbart, S.; Kelmer, E.; Shipov, A.; Shamir, M.H.
Summary: The ability to make an accurate prognosis, which is a prerequisite for treatment decisions, is very limited in dogs with traumatic brain injury (TBI). To determine whether serum concentrations of neuron-specific enolase (NSE) have prognostic value in dogs following TBI, we conducted a prospective, observational, controlled clinical study in an intensive care unit of a university teaching hospital. The study population comprised 24 dogs admitted to the hospital within 72 h of a known event of TBI between January 2010 and January 2015, as well as 25 control healthy shelter dogs admitted for elective neutering. Seventeen injured dogs (70%) survived to discharge, four were euthanized and three died within 48 h. Serum samples were obtained from all dogs (in injured dogs, within 72 h of TBI) and NSE concentrations were measured using enzyme-linked immonosorbent assay. Associations between NSE levels and outcome, Modified Glasgow Coma Scale, time to sampling, age or haemolysis scale were determined. Mean serum NSE concentrations were decreased in dogs with TBI compared with healthy controls (19.4 ± 4.14 ng/ml vs. 24.9 ± 4.6 ng/ml, P <0.001). No association was found between serum NSE concentrations and either survival or severity of neurological impairment. A negative correlation was found between serum NSE concentrations and time from trauma to blood collection (r = −0.50, P = 0.022). These results indicate that serum NSE concentration in dogs following TBI is not an effective marker for severity or outcome. Further studies are warranted to standardize serum NSE measurements in dogs and to determine the peak and half-life levels of this potential biomarker.